Objective Neurophysiological Measures of Cognitive Performance in Elite Ice Hockey Players - Kirby ED; Jones K; Campbell N; Fickling SD; D'Arcy RCN (Open Access Journal of Sports Medicine)
Eric D Kirby,1 Katherine Jones,2 Natasha Campbell,2 Shaun D Fickling,1,2 Ryan CN D’Arcy1– 3 1Brainnet, Faculty of Applied Sciences, Simon Fraser University, Metro Vancouver, BC, Canada; 2Centre for Neurology Studies, HealthTech Connex, Metro Vancouver, BC, Canada; 3DM Centre for Brain Health, University of British Columbia, Metro Vancouver, CanadaCorrespondence: Ryan CN D’Arcy, Centre for Neurology Studies, HealthTech Connex, Metro Vancouver, BC, Canada, Email Ryan@healthtechconnex.comIntroduction: Athletic peak performance is increasingly focused on cognitive and mental factors. In the current study, cognitive performance was measured by neurophysiological responses in elite Junior-A hockey players.Methods: Neurophysiological brain vital signs were extracted from event-related potentials (ERPs) to evaluate auditory sensation (the N100), basic attention (the P300), and cognitive processing (the N400). In total, we evaluated 348 athletes, across 17 teams, throughout different hockey arenas in British Columbia, Canada. While brain vital signs were collected to help manage concussion, the current investigation focused on a retrospective performance analysis of cognitive processing differences.Results: The results revealed three interesting findings: 1) Player position differences were detectable in sensory N100 latency, with significantly faster responses for forwards compared to defense; 2) Goalies showed significantly higher attention P300 amplitude compared to all other positions; and 3) Cognitive N400 processing differences were detectable only during competitive combine testing, showing 60ms latency differences between forwards and defense on average.Discussion: The current findings suggest that neurophysiological responses, which are also sensitive to concussion, may be used to identify sensory, attentional, and cognitive processing differences to help optimize peak performance.Keywords: electroencephalography, event-related potentials, brain vital signs, performance optimization, ice hockey